Involvement of the posterior visual pathway correlates with higher-order visual impairment in childhood stroke participants detected by virtual reality/eye-tracking paradigm - Da Cruz, Emily; Tambala, Diana; Lynch, Anna; Manley, Claire; Bambery, Melissa; Kelly, Daniel; Chui, Carrie; Alhadid, Kenda; Sullivan, Alyssa W.; Grieco, Julie; Ondeck, Benjamin; Lauer, Arne; et al. (Pediatric neurology, 2026)
Background - Cerebral injury due to stroke in childhood increases the risk of higher-order visual processing (HOVP) deficits, which can lead to behavioral and learning disabilities if left untreated. Using a virtual reality-based search task and structural magnetic resonance imaging analysis, we assess the extent of functional vision deficits in childhood stroke participants and potential anatomical correlates. - Methods - Twenty childhood stroke participants and 38 unimpaired controls completed a dynamic visual search task using a virtual reality/eye-tracking (VR/ET) paradigm to quantify functional vision abilities. Virtual reality assessment measures, stroke imaging characteristics, and neuropsychological outcomes were analyzed. - Results - All childhood stroke participants completed the VR/ET task with success rates and task compliance in equal measure to controls, and the task demonstrated association with neuropsychological testing measures of processing speed. Less accurate search, slower fixation rates, less sensitivity to task load changes, and greater delays initiating a response to a target were observed in our stroke cohort. On magnetic resonance imaging lesion analysis, injury involving the posterior visual pathways, specifically the optic radiations, inferior longitudinal fasciculus, or superior longitudinal fasciculus, correlated with slower reaction time when controlling for age at time of testing. - Conclusions - Bedside VR/ET assessment in children affected by stroke can detect signs of HOVP deficits identified in neuropsychological testing. Imaging demonstrating involvement of the posterior visual pathway is strongly correlated with impaired visual tracking ability development. Our study demonstrates that injury pattern on imaging at stroke diagnosis can help identify children at risk of HOVP deficits, enabling early monitoring and accommodations facilitating functional vision development.
Online veröffentlicht: 8. Oktober 2025
Gesehen am 17.02.2026